2017
DOI: 10.1021/acs.energyfuels.7b02796
|View full text |Cite
|
Sign up to set email alerts
|

Stability Assessment of Regenerated Hierarchical ZSM-48 Zeolite Designed by Post-Synthesis Treatment for Catalytic Cracking of Light Naphtha

Abstract: Hierarchical ZSM-48, a one-dimensional pore system zeolite with the presence of mesopores, was obtained by post-synthesis alkaline and acid treatments. Hierarchical ZSM-48 exhibited excellent hexane cracking activity compared to parent ZSM-48, which can be attributed to better diffusion as a result of the created mesoporosity. Moreover, the post-synthesis treatment allowed for manipulation of the distribution of active sites. Consequently, better stability and higher propylene selectivity were accomplished. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 31 publications
(57 reference statements)
1
27
0
Order By: Relevance
“…A higher acetone to glycerol ratio was obtained over a higher acetone to glycerol ratio. Both desilication and dealumination are very effective in improving the catalyst stability of zeolite based catalyst [66][67][68].…”
Section: Ketalization Of Glycerol Over Clay Mineralsmentioning
confidence: 99%
“…A higher acetone to glycerol ratio was obtained over a higher acetone to glycerol ratio. Both desilication and dealumination are very effective in improving the catalyst stability of zeolite based catalyst [66][67][68].…”
Section: Ketalization Of Glycerol Over Clay Mineralsmentioning
confidence: 99%
“…The low-cost fabrication of hierarchical zeolites with different topologies were started with three-dimensional (3D) medium pore ZSM-5 (MFI) (Muraza et al, 2013, 2014; Bawah et al, 2018), 3D large Beta (BEA) and 3D large pore FAU. Later, some one-dimensional pore zeolites such as MTW (Sanhoob et al, 2016), MTT (Muraza et al, 2013, 2014), TON (Jamil et al, 2018), and MRE (Ahmed et al, 2017) were also reported elsewhere.…”
Section: Perspective On Glycerol Over Hierarchical Zeolites In the Prmentioning
confidence: 97%
“…In addition to activation procedures, stability during chemical reactions, and possible regeneration are expected to suppress the catalyst cost. Ahmed and coworkers reported the decrease of crystallinity of hierarchical MRE zeolite (i.e., ZSM-48) (Ahmed et al, 2017). Typically, the crystallinity of zeolite-based catalysts decreased during regeneration.…”
Section: Glycerol Conversion Over Natural Mineralsmentioning
confidence: 99%
“…37 Up to date, it has been typically applied in n-heptane hydroisomerization, 38 methanol to hydrocarbons, 39 and catalytic cracking of light naphtha. 40 Due to the limited use of the one-dimensional framework of ZSM-48, there have been a few reports demonstrating its catalytic applications, especially when involving with a bulky molecule, such as glucose valorization. The intriguing strategy to overcome this restriction is to introduce the additional larger pores in the zeolite framework, which might open the opportunity of using one-dimensional ZSM-48 in many reactions in the future.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the ZSM-48 (*MRE topology) consists of a one-dimensional framework formed by 10-membered ring pores in the diameters of ∼5.6 × 5.3 Å . Up to date, it has been typically applied in n -heptane hydroisomerization, methanol to hydrocarbons, and catalytic cracking of light naphtha . Due to the limited use of the one-dimensional framework of ZSM-48, there have been a few reports demonstrating its catalytic applications, especially when involving with a bulky molecule, such as glucose valorization.…”
Section: Introductionmentioning
confidence: 99%